Methylmercury toxicity: amelioration by selenium and water‐soluble chelators as N‐acetyl cysteine and dithiothreitol. (13th January 2014) - Joshi, Deepmala; Mittal, Deepak Kumar; Shukla, Sangeeta; Srivastav, Ajai Kumar; Srivastav, Sunil Kumar
<x xml:space="preserve">Abstract</x> The protective potential of chelators, i.e. N‐acetyl cysteine (0.6 mg /kg, intraperitoneally) and dithiothreitol (15.4 mg kg−1, intraperitoneally) with selenium (0.5 mg kg−1, pre‐oral) were evaluated individually and in combination against methylmercury‐induced biochemical alterations and oxidative stress consequences. Forty‐two male Sprague–Dawley rats were exposed with methylmercury (1.5 mg kg−1, pre‐oral) daily for 21 days followed by different treatments for five consecutive days. Administration of methylmercury caused significant enhancement in the release of transaminases, alkaline phosphatases and lactate dehydrogenases in serum. A significant increased was observed in lipid peroxidation level with a concomitant decreased in glutathione content after methylmercury exposure in liver, kidney and brain. Hepatic microsomal drug metabolizing enzymes (aniline hydroxylase and amidopyrine N‐demethylase) of cytochrome p4502E1 showed sharp depletion after methylmercury exposure. Alterations in histological changes in liver, kidney and brain were also noted in methylmercury administered group. All treated groups showed recovery pattern, but the combined treatments with N‐acetyl cysteine and dithiothreitol in combination with selenium were more effective than that with either alone treatments in recovering blood biochemical changes after methylmercury toxicity. In conclusion, the results demonstrated that combination therapy may recover all blood biochemical alterations and offer maximum protection against methylmercury‐induced toxicity. Copyright © 2014 John Wiley & Sons, Ltd.